2023
DOI: 10.1002/cbic.202200797
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Ene‐Reduction by F420‐Dependent Oxidoreductases B (FDOR‐B) from Mycobacterium smegmatis

Abstract: Asymmetric reduction by ene‐reductases has received considerable attention in recent decades. While several enzyme families possess ene‐reductase activity, the Old Yellow Enzyme (OYE) family has received the most scientific and industrial attention. However, there is a limited substrate range and few stereocomplementary pairs of current ene‐reductases, necessitating the development of a complementary class. Flavin/deazaflavin oxidoreductases (FDORs) that use the uncommon cofactor F420 have recently gained atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…This is revolutionizing the diversity and metabolic potential of the archaea in a wide variety of environments, an important step toward understanding their ecological role and industrial applications. [12][13][14] The ancient coenzyme F420 is one of the important members of the ancient coenzymes and cofactors that participate in methanogenesis, sulfate-reduction, and methanotrophic reactions in archaea. 15,16 The coenzyme F420 is also present in a wide range of actinomycetes, mycobacteria, and other bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…This is revolutionizing the diversity and metabolic potential of the archaea in a wide variety of environments, an important step toward understanding their ecological role and industrial applications. [12][13][14] The ancient coenzyme F420 is one of the important members of the ancient coenzymes and cofactors that participate in methanogenesis, sulfate-reduction, and methanotrophic reactions in archaea. 15,16 The coenzyme F420 is also present in a wide range of actinomycetes, mycobacteria, and other bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] More recently, ene-reductases that utilize the deazaflavin cofactor F420 have been shown to reduce their substrates in a regio-and enantioselective manner that is often stereocomplementary to OYEs. [9][10][11] These enzymes belong to the flavin/deazaflavin oxidoreductase (FDOR) family of split β-barrel proteins. 12 While the cofactor F420 occurs only in a limited number of prokaryotes, elucidation of its biosynthesis and metabolic engineering has enabled its production in the industrial workhorse Escherichia coli (in which it is not natively produced) at high titers, creating opportunities for its use as a bio-orthogonal cofactor in biocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…24 We recently reported detailed characterization of the ene-reductase activity and substrate range of the FDOR enzymes from the -A and -B subgroups. 10, 11 Among the enzymes we have characterized, the FDOR-A enzymes MSMEG_2027 and MSMEG_2850 from Mycobacterium smegmatis demonstrated the best combination of activity and broad substrate range. 10 Using X-ray crystallography and computational substrate docking it was possible to identify the preferred binding mode of substrates in the active site, which when combined with the experimentally observed products suggested that reduction proceeds with net anti addition of H 2 across the double bond, as is most commonly observed in the OYE family.…”
Section: Introductionmentioning
confidence: 99%